A hydrophobic pervaporation membrane with hierarchical microporosity for high-efficient dehydration of alcohols. (12th October 2019) - Liu, Peng; Chen, Mengmeng; Ma, Yiqiang; Hu, Chuan; Zhang, Qiugen; Zhu, Aimei; Liu, Qinglin
Graphical abstract: Highlights: A synthetic strategy for hydrophobic polymer pervaporation membrane is presented. The membrane has the hierarchical structure of micropores-micropores-mesopores. The membrane shown high permeability and selectivity for dehydration of alcohols. Abstract: Pervaporation is a promising membrane technology for separation of aqueous organic solution particularly azeotrope and close-boiling point compounds. However, most of pervaporation membranes are based on hydrophilic polymers that suffer decline of separation performance due to their swelling in aqueous solution. Here we present a copolymer synthetic strategy for preparation of hydrophobic polymer pervaporation membrane with hierarchical porosity via uniting both rigid and flexible segments. The synthesized membrane has well-defined micropores and high free volume faction of 8.03% with cavity size of 0.476 nm, and demonstrate exceptional performance with high permeability and selectivity for dehydration of alcohols. In the pervaporation of ethanol-water azeotrope, the membrane displays the high permeabtion flux of 74.6 μm kg m −2  h −1 and water selectivity of 34 (separation factor of 732) at 30 °C. The developed strategy has excellent potential for synthesizing copolymers for high-efficient pervaporation membranes.